Assessment of housing affordability factor amongst B40 and M40 in Bintulu, Sarawak / Syazwani Shamsuddin - Shamsuddin, Syazwani (2020)
Housing affordability can be defined as the ability of the pbrson in term of the person saving, this not only for housing cost but also include other expenditure that contribute to their income. Limited supply of affordable house and inconsistent of house price increase and low income has led to unaffordable for own6rship of house. Due to the unaffordable level of house price, it is causing B40 and lV40 household cannot purchase their dream house. This research aim is to study what are the factor that affecting the housing affordability and as well as identify the methods to improve the issues of unatfordability of housing among B40 and lt/40 in Bintulu. To achieve the aim, the objectives of this study are to study what are the factors that affecting the housing affordability among 840 and tvl40 in Bintulu, to analyse the biggest factor that causing the unaffordability housing affordability among B40 and IVl40 in Bintulu and to identify the method to improve the factors of unaffordability housing affordability among 840 and M40 in Bintulu. For this study, it will be using questionnaire as the primary data and secondary data will be from literature review. The data that already been analyse in the SPSS software, form into table and pie chart. The finding of this study to identify biggest factor that causing the housing affordability and the method to improve it amongst B40 and M40 in Bintulu.